Differential chemotactic receptor requirements for NK cell subset trafficking into bone marrow - Bernardini, Giovanni; Sciumè, Giuseppe; Santoni, Angela (Frontiers in Immunology, 2013)
Responsiveness of maturing NK cells to chemotactic molecules directly affect their retention and relocation in selected BM microenvironment during development, as well as their localization at sites of immune response during inflammatory diseases. Bone marrow (BM) is the main site of NK cell generation, providing micro environmental signals required to sustain cell proliferation and differentiation. Drastic changes of expression and function of several chemoattractant receptors can be observed during progression from precursor NK cells to immature and mature NK cells. Indeed, the gradual decrease of CXCR4 expression parallels the increased expression of CXCR3, CCR1 and CX3CR1 and S1P5 on mature DX5+ NK cells. The chemokine CXCL12 is produced constitutively in the bone marrow and, acting via CXCR4, is critical for retaining immature and mature NK cell subsets in the BM. During steady-state, the maintenance of NK cells into BM parenchyma depends on the equilibrium of CXCR4 retention and S1P5 mobilizing functions, as the gradient of Sphingosine-1-phosphate coming from the sinusoids facilitates mature NK cell egress into circulation via S1P5, when CXCR4/CXCL12-mediated retention decreases. Chemoattractants are also key factors for the response to inflammatory or infection conditions that promote mobilization of effector NK cells from storage compartments (including BM) to sites of disease or for NK cell recruitment/response during pathological conditions that affect BM integrity, including haematopoietic malignancies. In this review, we summarize what is known about the requirement for NK cell localization and exit from BM and how chemokine-mediated functions may affect BM NK cell development and immune responses.